Effects of the Application Methods and Concentrations of Sucrose Solution on Growth and Antioxidant Activity of Sunflower Sprouts - Koodkaew, Intira; Tungkasem, Benjamart (Burapha Science Journal, 2026)
The objective of this study was to determine the application methods and concentrations of sucrose solution on growth and antioxidant activity in sunflower sprout. The experiments were provided as two experiments, experiment 1, comparison between the spraying rate and concentrations of sucrose solution, and experiment 2, comparison between the duration of incubated-seed soaking and concentration of sucrose solution. The experiments were assigned as 3×5 factorial in completely randomized design with three replications. The growth parameters, stem length, fresh weight and dry weight as well as antioxidant activity by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method, were determined. The results of the experiment 1 showed that sucrose spraying for 5 days with 20 mL daily at 25, 50, 100 and 200 mM significantly enhanced the antioxidant activity in the sunflower sprout (60.10, 40.37, 67.34 and 77.08% higher than the control, respectively) without adverse effect on sunflower sprout growth. The results of experiment 2 showed that incubated-seed soaking in 25 and 50 mM sucrose for 10 min significantly increased the antioxidant activity in the sunflower sprout (72.17 and 204.82% higher than the control, respectively) and had no effect on sprout length and weight. The results of this study indicated that application of sucrose solution by spraying and soaking methods with suitable concentration had potential to improve antioxidant activity in sunflower sprout.